ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PERUSAHAAN PADA PT MIDI UTAMA INDONESIA TBK PERIODE 2020-2024 - Adinna Salsabela; Haryo Kusumo; Febryantahanuji (LPPM Universitas Sains dan Teknologi Komputer, 2025)
The retail industry is highly influenced by the level of consumer spending, which experienced significant changes during the Covid-19 pandemic. PT Midi Utama Indonesia Tbk, as one of the leading retail companies, has sought to maintain its performance through service improvement, technological innovation, and financial management. This study aims to analyze the financial performance of PT Midi Utama Indonesia Tbk for the period 2020–2024 using profitability ratios, including Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE). The results show that both NPM and ROA recorded positive trends until 2023, with NPM peaking at 3.01% and ROA at 6.71%, although both remain below industry standards. Meanwhile, ROE reached its highest level in 2022 at 20.21% before declining in subsequent years. The simultaneous decrease in all ratios in 2024 indicates pressure on net income due to rising costs and imbalances between revenue, assets, and equity growth. Overall, PT Midi Utama Indonesia Tbk demonstrated gradual profitability improvement up to 2023; however, cost control, asset optimization, and balanced capital management strategies are required to sustain future growth.